Weak‐Turbulent Theory of Wind‐Driven Sea. Issue 4 (9th April 2019) - Zakharov, Vladimir E.; Badulin, Sergei I.; Geogjaev, Vladimir V.; Pushkarev, Andrey N.
Abstract : We present a self‐consistent analytic theory of the wind‐driven sea—the weak‐turbulent theory. The base statement of the theory is that the four‐wave resonant interactions play the leading role in the energy balance of the wind‐driven sea. We study the exact solution of the stationary wave kinetic equation and the self‐similar solutions of wave kinetic equation both in fetch‐ and duration‐limited cases. The theory makes possible to explain the nature of universal power‐like energy spectra as well as the power‐like dependence of the total wave energy and peak frequency from the fetch and the duration. Key Points: The analytical theory of wind‐driven sea is developed The theoretical results are supported by numerical studies and experimental facts A new numerical algorithm for the kinetic equation is proposed